FINANCIAL INSTITUTIONS WITHIN THE ECOSYSTEM OF SUSTAINABLE DIGITAL FINANCIAL ASSETS AS AN ELEMENT OF THE TRIPLE HELIX MODEL IN THE AGRO-INDUSTRIAL SECTOR - Zhdanova, Olga (Veredas do Direito, 2026)
Today, several major trends are shaping the world, most notably digitalization, sustainable development, and the ecosystem approach. Digitalization is spreading across nearly all areas of economic and social activity, fundamentally changing how economic actors interact. One of the key drivers of this shift is the emergence of new financial instruments, particularly digital financial assets. Sustainable development focuses on achieving environmental and social well-being. It is closely connected to the agro-industrial sector, which plays a critical role in food production. The ecosystem approach complements these trends by offering a more holistic way to understand and manage development. These three trends can be viewed within a single framework, i.e. the sustainable digital financial asset market. This ecosystem brings together various participants and elements, along with their internal and external relationships. It considers technical, financial, economic, and legal aspects as part of a unified system. Sustainable digital financial assets (green, social, and environmental and social well-being) represent digital rights in the form of monetary claims. They are issued, recorded, and traded exclusively through distributed ledger systems. The funds raised from these instruments must be used to support projects that contribute to sustainable development. The agro-industrial sector remains one of the core pillars of the economy, as it ensures food security and meets basic human needs. Integrating financial institutions from the sustainable digital financial asset ecosystem into a modified triple helix model can create additional synergies. In practice, this would expand access to financing for both large agricultural enterprises and smaller producers within the sector.